THE IMPACT OF ONLINE ADVERTISING USING THE FACEBOOK PLATFORM ON ONLINE PRODUCT PURCHASE DECISIONS IN STIE RAHMANIYAH SEKAYU STUDENTS - Hendry Wijaya; Dadang Syaputra; Heni Ulpa (Jurnal Ilmiah Publipreneur, 2022)
The aim of this study is to explain how online advertising via Facebook influences the decision to buy online products for STIE Rahmaniyah Sekayu students. The sample uses the Slovin formula. The data collection method used a questionnaire to the STIE Rahmaniyah Students of the Management Study Program and the Accounting Study Program. Data were analyzed using the Quantitative Method using SPSS 20.0 for windows software. The results of the study show that in data analysis it can be seen that the advertising regression coefficient (X) is 0.289 indicating that every time there is an addition to an online purchase decision of 1 unit, while the other variables are constant, this will affect the online purchase decision by 0.289. The coefficient is positive, meaning that there is a positive relationship between advertising (X) and online purchase decisions (Y) (Case Study in Management Students at STIE Rahmaniyah Sekayu). The correlation coefficient of 0.226 indicates that there is a positive but not too strong or not too influential relationship between advertising variables via Facebook social media and online purchase decisions. Besides that, the determinant correlation coefficient of 0.051 shows that the advertising variable through Facebook social media in this study is able to explain 5.1% of online purchasing decisions, while the rest is explained by other variables outside this study. Based on the results of hypothesis testing (t test), it is known that the value of tcount is 2.109 while ttable is 1.9882, because the value of tcount ttable is (2.109 1.9882), then HO is rejected and Ha is accepted. This means that there is an influence of advertising through Facebook social media on online product purchasing decisions. Keywords: Work Culture, Work Environment, Work Motivation, Path Analysis